Chemical bath deposition of CdS quantum dots on vertically aligned ZnO nanorods for quantum dots-sensitized solar cells - Lee, Wonjoo; Min, Sun Ki; Dhas, Vivek V.; Ogale, Satishchandra B.; Han, Sung-Hwan (Electrochemistry Communications, 2009)
Formation of US quantum dots (Q dots) on the vertically aligned ZnO nanorods electrode was carried out by chemical bath deposition. The diameter and thickness of ZnO nanorods are similar to 100-150 nm and similar to 1.6 mu m, respectively, and CdS Q dots on ZnO nanorods have a diameter of smaller than 15 nm. In application of the Q dots-sensitized solar cells, composite film exhibited a power conversion efficiency of 0.54% under air mass 1.5 condition (80 mW/cm(2)), and incident-photon-to-current conversion efficiency showed 18.6%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical bath deposition; Photosensitization; quantum dots; solar cells; Wet-chemical process